Mapping physiological G protein-coupled receptor signaling pathways reveals a role for receptor phosphorylation in airway contraction - Bradley,SJ; Wiegman,CH; Iglesias,MM; Kong,KC; Butcher,AJ; Plouffe,B; Goupil,E; Bourgognon,J-M; Macedo-Hatch,T; LeGouill,C; Russell,K; Laporte,SA; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
G protein-coupled receptors (GPCRs) are known to initiate a plethora of signaling pathways in vitro. However, it is unclear which of these pathways are engaged to mediate physiological responses. Here, we examine the distinct roles of Gq/11-dependent signaling and receptor phosphorylation-dependent signaling in bronchial airway contraction and lung function regulated through the M3-muscarinic acetylcholine receptor (M3-mAChR). By using a genetically engineered mouse expressing a G protein-biased M3-mAChR mutant, we reveal the first evidence, to our knowledge, of a role for M3-mAChR phosphorylation in bronchial smooth muscle contraction in health and in a disease state with relevance to human asthma. Furthermore, this mouse model can be used to distinguish the physiological responses that are regulated by M3-mAChR phosphorylation (which include control of lung function) from those responses that are downstream of G protein signaling. In this way, we present an approach by which to predict the physiological/therapeutic outcome of M3-mAChR–biased ligands with important implications for drug discovery.